Electrophysiological Signatures of Numerosity Encoding in a Delayed Match-to-Sample Task - Fu, Wanlu; Dolfi, Serena; Decarli, Gisella; Spironelli, Chiara; Zorzi, Marco (Frontiers in Human Neuroscience, 2022)
The number of elements in a small set of items is appraised in a fast and exact manner, a phenomenon called subitizing. In contrast, humans provide imprecise responses when comparing larger numerosities, with decreasing precision as the number of elements increases. Estimation is thought to rely on a dedicated system for the approximate representation of numerosity. While previous behavioral and neuroimaging studies associate subitizing to a domain-general system related to object tracking and identification, the nature of small numerosity processing is still debated. We investigated the neural processing of numerosity across subitizing and estimation ranges by examining the electrophysiological activity during the memory retention period in a delayed numerical match-to-sample task. We also assessed potential differences in the neural signature of numerical magnitude in a fully non-symbolic or cross-format comparison. In line with behavioral performance, we observed a modulation of parietal-occipital neural activity as a function of numerosity that differed in the two ranges, with distinctive neural signatures of small numerosities showing clear similarities with those observed in visuospatial working memory tasks. We also found differences in neural activity related to numerical information in anticipation of single vs cross-format comparison, suggesting a top-down modulation of numerical processing. Finally, behavioral results revealed an enhanced performance in the mixed-format condition and a significant correlation between task performance and symbolic mathematical skills. Overall, we provide evidence for distinct mechanisms related to small and large numerosity and differences in numerical encoding based on task demands.